A Note on The Genus Evolvulus (Convolvulaceae) In Java, Indonesia - Irsyam, Arifin Surya Dwipa; Hariri, Muhammad Rifqi; Irwanto, Rina Ratnasih; Mustaqim, Wendy Achmad (Jurnal Biodjati, 2020)
According to the Flora of Java, there isÂ only one species of Evolvulus in Java, namely Evolvulus alsinoides. Since then, a second species was reported in 2017 from Universitas Indonesia, Depok, West Java, as an alien naturalized species.Â Some recent field studiesÂ have been conductedÂ to provide updatedÂ taxonomic information of the genus on this island. The field observations were carried out in Banten, Jakarta, West Java, Jogjakarta, and East JavaÂ from MarchÂ to December 2019.Â The herbarium studies were also conducted in Herbarium Bogoriense, Herbarium of Bogor Botanic Gardens, Herbarium Bandungense, and Herbarium of the Department of Biology, Universitas Indonesia. Our study reveals oneÂ newly recorded species of Evolvulus in JavaÂ already grown in cultivation, namely E. glomeratus Nees & Mart. subsp.Â grandiflorus (Parodi) Ooststr.Â Besides that, EvolvulusÂ nummularius is now also reported to occur in other sites of West Java and extended to Central Java. An updated key to Evolvulus in Java, descriptions to both species, photographs, and brief discussions are provided.